Management of Patients Who Seek Urologic Care in Covid-19 Pandemic Era - Tonyali, Senol; Haberal, Hakan Bahadir; Ergul, Rifat; Dursun, Murat (Urology Journal, 2020)
Introduction: Novel coronavirus Disease (Covid-19) has emerged in Wuhan, China in December 2019 and became a pandemic in a few weeks. In this review, we aimed to summarize the current urologic practice trends worldwide to help urologist in decision making in disasters particularly in Covid-19 pandemic. Material and Method: We have performed a PubMed and Internet search by using the keywords: ‘Covid’, ‘new coronavirus’, ‘coronavirus urology, ‘covid urology’ without a date restriction. Results: All elective surgeries for benign urological conditions such as urinary tract stone disease that not caused complicated obstruction, benign prostate enlargement, infertility, incontinence and genitourinary prolapse, erectile dysfunction undescendent testis, vesico-ureteral reflux should be postponed till the lasting of Covid-19 outbreak. In obstructing ureteral stone both nephrostomy tube and double-J stent insertion are valid management options. However, one must consider that these procedures must be performed under local anesthesia when possible to spare a ventilator. When deferring urooncological operations and treatments oncological outcomes must be considered. Aggressive cessation or reducing the dosage of immunosuppressant therapy might be an option in renal transplanted patients with severe pneumonia or acute respiratory distress syndrome.